2012
DOI: 10.1007/s00221-012-3290-6
|View full text |Cite
|
Sign up to set email alerts
|

Orbicularis oculi muscle activation during swallowing in humans

Abstract: Intraoral trigeminal afferents elicit EMG activity from the lower facial muscle, orbicularis oris (OR) during swallowing. The upper facial muscles and especially orbicularis oculi (OC) were not previously known to be associated with deglutitional events. Nevertheless, given the large area of intraoral mucosa and teeth innervated by the trigeminal nerve afferents, a connection between OC motoneurons and deglutition may theoretically be expected, which we sought to evaluate in this study. Healthy controls were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…The oral phase parameters of the VDS include lip closure, bolus formation, and mastication, for which performance of the facial muscles is important. Facial muscles are involved in mastication of food and in formation of intraoral pressure during the oral phase and play a role in preventing the leaking of food via lip closure9 ) . Therefore, the present study demonstrated that improvement in the strength of facial muscles contributed to improvement in the oral phase of swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…The oral phase parameters of the VDS include lip closure, bolus formation, and mastication, for which performance of the facial muscles is important. Facial muscles are involved in mastication of food and in formation of intraoral pressure during the oral phase and play a role in preventing the leaking of food via lip closure9 ) . Therefore, the present study demonstrated that improvement in the strength of facial muscles contributed to improvement in the oral phase of swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…There are precedents for such regulation, as functional linkage has been demonstrated between the orbicularis oculi and the orbicularis oris by several authors (e.g. Ertekin, Eryasar, Gürgör, Arici, Secil, & Kurt, 2013). Additionally, Morecraft, Stilwell-Morecraft, and Rossing (2004) reported clinical observations that indicate a higher oral regulation of facial expression -both voluntary and emotionalthat does not occupy a specific site in the brain or manifest through a single neural projection system.…”
Section: Discussionmentioning
confidence: 98%
“…Ertekin, Eryasar, Gürgör, Arici, Secil, and Kurt (2013) reported that the orbicularis oris and the orbicularis oculi were intermittently synchronized with swallowing. They proposed that some reflexes, like those related to swallowing, originate partly from the intraoral trigeminal afferents.…”
Section: Discussionmentioning
confidence: 99%
“…There is no strong evidence of a cortical influence on SS in humans. SS is composed of periodic swallowing movements spread out over 24 hours (27,(31)(32)(33)(34). The pacemaker for SS seems to be related to the CPG of the brainstem network (17,18).…”
Section: Voluntary Versus Spontaneous Swallowingmentioning
confidence: 99%